2016
DOI: 10.1155/2016/8360738
|View full text |Cite
|
Sign up to set email alerts
|

AP39, a Mitochondria‐Targeted Hydrogen Sulfide Donor, Supports Cellular Bioenergetics and Protects against Alzheimer’s Disease by Preserving Mitochondrial Function in APP/PS1 Mice and Neurons

Abstract: Increasing evidence suggests that mitochondrial functions are altered in AD and play an important role in AD pathogenesis. It has been established that H2S homeostasis is balanced in AD. The emerging mitochondrial roles of H2S include antioxidation, antiapoptosis, and the modulation of cellular bioenergetics. Here, using primary neurons from the well-characterized APP/PS1 transgenic mouse model, we studied the effects of AP39 (a newly synthesized mitochondrially targeted H2S donor) on mitochondrial function. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 71 publications
2
41
0
Order By: Relevance
“…Currently, AP39, which appears to be a more effective H 2 S releaser than AP123 (Gerö et al, 2016), has been studied more extensively. Interestingly, and consistently with the positive bioenergetic effects of low concentrations of H 2 S, low concentrations of AP39 (25-100 nM) induced an elevation in basal mitochondrial activity (basal respiration and maximal respiration) of cultured endothelial cells and neurons, whereas at higher concentrations (250-300 nM) this effect is no longer detectable (Szczesny et al, 2014;Zhao et al, 2016a), consistent with the bell-shaped mitochondrial action of H 2 S. Mitochondrial H 2 S delivery with AP39 improved mitochondrial function in oxidatively stressed cells, at least in part due to the fact that it reduced mitochondrial ROS levels (Szczesny et al, 2014;Karwi et al, 2017). In addition, AP39 and AP123 also improved mitochondrial DNA repair in oxidatively stressed cells (Szczesny et al, 2014, Ger} o et al, 2016.…”
Section: Mitochondrially Targeted H 2 S Donorsmentioning
confidence: 60%
See 2 more Smart Citations
“…Currently, AP39, which appears to be a more effective H 2 S releaser than AP123 (Gerö et al, 2016), has been studied more extensively. Interestingly, and consistently with the positive bioenergetic effects of low concentrations of H 2 S, low concentrations of AP39 (25-100 nM) induced an elevation in basal mitochondrial activity (basal respiration and maximal respiration) of cultured endothelial cells and neurons, whereas at higher concentrations (250-300 nM) this effect is no longer detectable (Szczesny et al, 2014;Zhao et al, 2016a), consistent with the bell-shaped mitochondrial action of H 2 S. Mitochondrial H 2 S delivery with AP39 improved mitochondrial function in oxidatively stressed cells, at least in part due to the fact that it reduced mitochondrial ROS levels (Szczesny et al, 2014;Karwi et al, 2017). In addition, AP39 and AP123 also improved mitochondrial DNA repair in oxidatively stressed cells (Szczesny et al, 2014, Ger} o et al, 2016.…”
Section: Mitochondrially Targeted H 2 S Donorsmentioning
confidence: 60%
“…16G) and a related compound AP123 combine the well-known mitochondrial targeting moiety triphenylphosphonium (TPP + ) with a dithiolethione H 2 S delivery moiety. AP39 and AP123, as expected, selectively increase the H 2 S signal in the mitochondrial compartment of cultured cells (Le Szczesny et al, 2014;Montoya and Pluth, 2016) and exert cytoprotective effects in various cell types (e.g., endothelial cells, epithelial cells, platelets, neurons, cardiac myocytes) against various forms of oxidative stress (H 2 O 2 , rotenone, glucose oxidase, elevated extracellular glucose, anoxia/reoxygenation) in vitro in high nanomolar/low micromolar concentrations (D'Araio et al, 2014Le Trionnaire et al, 2014Szczesny et al, 2014;Emerson et al, 2015;Sitek et al, 2015;Ahmad et al, 2016a;Chatzianastasiou et al, 2016;Ger} o et al, 2016;Zhao et al, 2016a;Lobb et al, 2017). Currently, AP39, which appears to be a more effective H 2 S releaser than AP123 (Gerö et al, 2016), has been studied more extensively.…”
Section: Mitochondrially Targeted H 2 S Donorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Nagahara et al generated an MST knockout mouse [ 57 ] which showed neuromental dysfunction comparable to the neuropsychiatric abnormalities which are the early signs of vitamin B 12 or folic acid deficiency. Also, a recent series of reports showed curative effects of a sulfur donor in mouse models of Alzheimer’s disease (see [ 58 ]). The sulfur donor, triphenylphosphonium-(CH 2 ) 9 -C(O)- O -phenyldithiolethione, called AP39, is an ester that is likely to be lipid soluble and to pass through the blood-brain barrier and to supply supplemental sulfur to the brains of the mice.…”
Section: Putting the Information Togethermentioning
confidence: 99%
“…In the central nervous system, the production of endogenous H 2 S is mainly catalyzed by cystathionine-β-synthase (CBS) [13]. Exogenous H 2 S inhibited the expression of pro-in ammatory factors and decreased the generation of oxidative indicator reactive oxygen species in the mouse model of Alzheimer's disease [14,15]. However, it has not been fully investigated the effects and mechanisms of H 2 S on the in ammation in neurons under hyperglycemia.…”
mentioning
confidence: 99%